(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Many open source web based e-Learning systems are offered to support learning environment over the internet. Academic institutions usually choose to implement systems that meet the needs and characteristics of students. However, only little guide exists to support them in choosing systems that meet the implicit needs of students, thus adoption of e-Learning system is unsustainable. This paper reports an attempt to discover these implicit needs and how it correlates to the design of e-Learning systems by the adoption of Kansei Engineering. The objective is to analyze and choose the desired open source e-Learning system based on studentsâ€™ implicit needs. Five open source e-Learning system were used as specimen in a Kansei evaluation procedure, employing one hundred subjects from the target user group. The result suggests that Kansei Engineering can be used to determine open source e-Learning systems that meets the implicit needs of targeted users, and thus enable sustainability of the system implementation.Â